2006
DOI: 10.4049/jimmunol.176.12.7394
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of ICOS on Graft-versus-Host Disease Mediated by CD4 and CD8 T Cells

Abstract: ICOS, a CD28 family member expressed on activated CD4+ and CD8+ T cells, plays important roles in T cell activation and effector function. Here we studied the role of ICOS in graft-vs-host disease (GVHD) mediated by CD4+ or CD8+ T cells in allogeneic bone marrow transplantation. In comparison of wild-type and ICOS-deficient T cells, we found that recipients of ICOS−/− CD4+ T cells exhibited significantly less GVHD morbidity and delayed mortality. ICOS−/− CD4+ T cells had no defect in expansion, but expressed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 44 publications
4
20
0
Order By: Relevance
“…The latter concept is supported by our data obtained in in-vitro apoptosis assays revealing that T cell stimulation in the presence of ICOS agonist predisposes CD8 + (but not CD4 + ) T cells for death by apoptosis ( Figure 2 ). This is well in line with another study that demonstrated differential effects of ICOS on CD4 + and CD8 + T cells with an increased ability of ICOS −/− CD8 + T cells to induce Graft-versus-Host Disease (GvHD) as a result of enhanced survival and expansion of those cells [40].…”
Section: Discussionsupporting
confidence: 89%
“…The latter concept is supported by our data obtained in in-vitro apoptosis assays revealing that T cell stimulation in the presence of ICOS agonist predisposes CD8 + (but not CD4 + ) T cells for death by apoptosis ( Figure 2 ). This is well in line with another study that demonstrated differential effects of ICOS on CD4 + and CD8 + T cells with an increased ability of ICOS −/− CD8 + T cells to induce Graft-versus-Host Disease (GvHD) as a result of enhanced survival and expansion of those cells [40].…”
Section: Discussionsupporting
confidence: 89%
“…Given that un-programmed CD8 + T cells deficient in ICOS expand to a greater extent than WT counterparts in a GVHD model (29), we hypothesized that Tc17 (but not Th17) cells deficient in ICOS would expand to a greater extent than WT Tc17 cells. Indeed, ICOS −/− Tc17 cells expanded to a slightly greater extent than WT Tc17 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This proliferative effect of ICOS costimulation is not appreciable during in vivo immune responses presumably due to a dominant effect of CD28 (3). However, ICOS does play critical roles in generation of follicular Th cells (4), antitumor T cell responses (5), and graft-versus-host disease (GVHD) (69). These impacts are related to augmented expression of an array of Th1 and Th2 cytokines, including IFN-γ, IL-4, IL-10, and IL-21 by ICOS costimulation.…”
mentioning
confidence: 99%
“…Results from another group indicated that ICOS blockade reduced GVHD while largely sparing graft-versus-leukemia activity by skewing toward Th2 differentiation, without affecting T cell activation, proliferation, cytotoxicity, and target organ infiltration (6). Studies by our own group indicate that ICOS deficiency or blockade results in significantly less GVHD morbidity and delayed mortality (7, 9). The effect of ICOS is predominately on CD4 T cells, and the deficiency of ICOS had no impact on their expansion, but significantly reduced their effector functions in term of expression in FasL and production of IFN-γ and TNF-α (9).…”
mentioning
confidence: 99%